Rheological and textural insights into the blending of sweet potato and cassava starches: In hot and cooled pastes as well as in fresh and dried gels. (April 2019) - Li, Shuanghong; Ye, Fayin; Zhou, Yun; Lei, Lin; Zhao, Guohua
Abstract: Starches from different origins are often blended with the aim of lowering cost and modulating product texture. However, the law governing the blending consequence is not well established. To this end, the pastes, fresh and dried gels from the blends of sweet potato starch (SPS) with cassava starch (CS) at different ratios were investigated. The results revealed that SPS and CS largely differ in terms of pasting behavior, rheological properties of hot and cooled paste as well as the textural parameters of fresh and dried gels. Generally, there are two categories, namely additive and non-additive for the blending effects of different starches. The present study shows that the blending effect of SPS and CS highly depends on the ratios of individual components and is also property specific. The pasting behavior during peak viscosity development is of non-additive nature but the remaining part is governed by an additive law. In hot and cooled blend pastes, the individual starches behave independently in steady shear measurements while they interact more or less in dynamic oscillatory shear measurements, thus demonstrating additive and non-additive effects, respectively. As for fresh and dried blend gels, additive effects were concluded for most tested textural parameters and physicochemical properties except for the enthalpy of dried ones and the elasticity of the cooked ones. This study provides basis to formulate the blend of SPS and CS with particular functionalities. Graphical abstract: Highlights: Sweet potato starch (SPS) differs from cassava starch (CS) in diverse functionalities. A non-additive pasting behavior was observed for the blends before peak development. Both hot and cooled blend pastes non-additively behavior in steady shear measurements. The blending effects in paste viscoelasticity are parameter and blending ratio specific. The blends show additive effects in most textural parameters of fresh and dried gels.